Comparative evaluation of antidotal efficacy of 2-PAM and HNK-102 oximes during inhalation of sarin vapor in Swiss albino mice. (3rd July 2018) - Swami, Devyani; Yadav, Ruchi; Bhaskar, A.S.B.; Soni, A.; Nagar, D.P.; Acharya, J.; Karade, H.N.; Singh, K.P.; Kumar, Pravin
Abstract: Efficacy of two oximes treatments evaluated during inhalation of sarin vapor (LCt50, 755.9 mg/min/m 3 ) in simulated real scenario in vivo . Majority of mice either became moribund or died within 1–2 min during exposure to multifold-lethal concentrations of sarin vapor. Protection indices were determined by exposing to sarin vapor in two sessions, 1 min exposure followed by treatments with or without HNK-102 (56.56 mg/kg, im) or 2-PAM (30 mg/kg, im) and atropine (10 mg/kg, ip), and again exposed for remaining 14 min. Protection offered by HNK-102 was found to be four folds higher compared to 2-PAM in the same toxic environment. Secondly, sub-lethal concentration of sarin vapor (0.8 × LCt50 or 605 mg/min/m 3 ), 24 h post investigations revealed that the oximes could not reactivate brain and serum acetylcholinesterase (AChE) activity. The treatments prevented increase in protein concentration ( p  < .05) and macrophages infiltration compared to sarin alone group in broncho-alveolar lavage fluid. Lung histopathology showed intense peribronchial infiltration and edema with desquamating epithelial lining and mild to moderate alveolar septal infiltration in sarin and atropine groups, respectively. Noticeable peeling-off observed in epithelial lining and sporadic mild infiltration of epithelial cells at bronchiolar region in 2-PAM and HNK-102 groups, respectively. The oximes failed to reactivate AChE activity; however, the mice survived up to 6.0 × LCt50, proved involvement of non-AChE targets in sarin toxicity. Atropine alone treatment was found to be either ineffective or increased the toxicity. HNK-102, exhibited better survivability with lung protection, can be considered as a better replacement for 2-PAM to treat sarin inhalation induced poisoning.